2007
DOI: 10.1039/b710026d
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hydrogen storage in Ni/Ce composite oxides

Abstract: The properties of dried (but not calcined) coprecipitated nickel ceria systems have been investigated in terms of their hydrogen emission characteristics following activation in hydrogen. XRD and BET data obtained on the powders show similarities to calcined ceria but it is likely that the majority of the material produced by the coprecipitation process is largely of an amorphous nature. XPS data indicate very little nickel is present on the outermost surface of the particles. Nevertheless, the thermal analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It has been reported that CeO 2 improves the catalytic performance of nickel for CO 2 reforming into methane, because it prevents coke formation and increases the stability of Ni nanoparticles . Further benefit comes from the strong metal–support interaction between Ni and ceria, which alters the electronic and chemical properties of Ni. In spite of numerous investigations, the mechanism of CO 2 activation over metal/ceria catalysts is still under debate at the molecular level. For instance, Bradford and Vannice described a hydrogen-assisted CO 2 activation mechanism via a carbonate intermediate in the metal–support interfacial region .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that CeO 2 improves the catalytic performance of nickel for CO 2 reforming into methane, because it prevents coke formation and increases the stability of Ni nanoparticles . Further benefit comes from the strong metal–support interaction between Ni and ceria, which alters the electronic and chemical properties of Ni. In spite of numerous investigations, the mechanism of CO 2 activation over metal/ceria catalysts is still under debate at the molecular level. For instance, Bradford and Vannice described a hydrogen-assisted CO 2 activation mechanism via a carbonate intermediate in the metal–support interfacial region .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Ni-CeO 2 composite coatings have been widely used as an active catalyst for partial oxidation of methane [14][15][16], hydrogen production and storage [17][18][19]. Ni-cerium oxide composite coatings also have favorable physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Compared with the gas cylinders, metal hydrides have attracted lots of attention around the world due to the advantages of much higher volume density (70-150 kg m À3 ), more satisfying safety performance, much higher hydrogen purity, and much lower moderate operating conditions. [3][4][5][6][7][8][9][10][11][12] In recent years, the La-Mg-Ni based hydrogen storage alloys, especially the alloys with superlattice structures of AB 3 -, A 2 B 7and A 5 B 19 type, have been a focus of studies. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] These structures possess characteristic layered structure consisting of one MgZn 2 -type (A 2 B 4 ) cell and one to three CaCu 5 -type (AB 5 ) cells stacking along c-axis, which are considered as the promising candidates to replace current AB 5 -type alloys as negative electrodes of MH-Ni batteries.…”
Section: Introductionmentioning
confidence: 99%